Food for An Urban Planet: Entry Points for World Bank Investments for Healthy and Resilient City Food Systems - Giertz, Åsa; Prain, Gordon; Alonso, Silvia; Claereboudt, Etienne; Davis, Madison; Kamm, Christian Leahy; Nagpal, Gauri; Gavazzeni, Filippo; Jonasova, Marketa (CGIAR System Organization, 2025)
Urban food systems are at the center of the social and cultural web that characterizes cities, and key contributors to economic growth, job creation, and local innovation that also influences surrounding regions (World Bank 2009). Today, more than half of the world’s population, about 4.3 billion people, live in urban areas. By 2050, 68 percent (6.5 billion people) will be living in cities, with 90 percent of this growth occurring in low- and middle-income countries (United Nations, 2018). This urban expansion come with its challenges, yet it also brings huge opportunities for people to benefit more from the urban food system. Eighty percent of the world’s food is already consumed in urban areas1 and urban food systems are recognized “as active drivers of positive transformation” (Abdullah 2019). Vast tracts of agricultural land are situated within cities and at the peri-urban interface. Many of these productive greenspaces within and around cities have economic potential because of their man uses, for example as sites of local tourism and recreation, with low-cost restaurants and eateries dotted across the agricultural space (Zasada 2011). This urban and peri-urban food production is linked to urban markets through a plethora of inventive transport businesses, from low-investment tricycles to trucking operations. Wet markets, which supply most of the food to lower income urban residents, function in the face of massive congestion in inner city areas, thanks to innovative wholesalers with multiple supply sources, informal food vendors working long hours, and the efforts of market managements. For consumers in urban areas lacking cooking facilities or working multiple jobs in distant parts of the city or working on low incomes that preclude use of restaurants at midday, a vast army of informal street food vendors provide a wide range of dishes at low cost. Even the food waste sector is a source of formal and informal employment. Cities are also a hub for talented youth looking for new business opportunities, responding to the massive level of demand for services that exist in urban areas.